A rare case of occipital plexiform neurofibroma with skull erosions in neurofibromatosis type 1 - Kumanan, T.; Mathangi, N.; Suganthan, N.; Brammah, R.T. (Sri Lanka College of Internal Medicine, 2026)
Plexiform neurofibromas are benign nerve sheath tumours commonly associated with neurofibromatosis type 1 (NF1). Plexiform neurofibromas of the scalp is a rare finding. Plexiform neurofibroma in the occipital region is even rarer. The commonest skull manifestations in neurofibromatosis involve the orbit, with very few reports about occipital defects. Magnetic resonance imaging (MRI) is the preferred modality to identify the lesion. It is usually managed by surgical excision, but recurrence has also been reported even after thorough removal. We present a case of a 52-year-old man with plexiform neurofibroma in the occipital region with skull erosions which is an extremely rare finding
Keywords: Plexiform neurofibroma; Bone erosions; Neurofibromatosis type 1 (NF1); Occipital plexiform neurofibroma